Standardization in building: a review of MS1184:2014 - Abdul Rahim, Asiah; Abd. Samad, Nur Amirah (2014)
The objective of this paper is to state the history of the application of universal design in Malaysia. In 1957, Malaysia gain independence, in late 1980s, the development of Malaysian Standards and code of practices on access for the disabled were initiated. Department of Standards Malaysia and IIUM have launched the new edited Malaysian Standards (MS 1184:2014) Universal Design and Accessibility in the Built Environment-Code of Practice for the public. KUDU IIUM has conducted access audit of existing buildings to measure the level of access and making all spaces and facilities safe and usable by all people.